Graphene-TMD Van der Waals Heterostucture Plasmonics - Goswami, P.; Tyagi, U. P. (Journal of Scientific Research, 2020)
The collective excitations of electrons in the bulk or at the surface, viz. plasmons, play an important role in the properties of materials, and have generated the field of “plasmonics”. We report the observation of a highly unusual plasmon mode on the surface of Van der Waals heterostructures (vdWHs) of graphene monolayer on 2D transition metal dichalcogenide (Gr-TMD) substrate. Since the exponentially decaying fields of surface plasmon wave propagating along interface is highly sensitive to the ambient refractive index variations, such heterostructures are useful for ultra-sensitive bio-sensing.